Pharmacokinetics and bioavailability of tolfenamic acid in sheep - Corum, Orhan; Corum, Duygu Durna; Er, Ayse; Yildiz, Ramazan; Uney, Kamil (Wiley, 2018)
AbstractThe pharmacokinetics, bioavailability, and tolerability of tolfenamic acid (TA) were determined after treating sheep withTAvia different routes and doses. This crossover study was carried out with a washout period of 15 days. In the study, 16 clinically healthy sheep were randomly assigned to two equal groups. In the first group (n = 8), animals receivedTAby intravenous (IV), intramuscular (IM), subcutaneous (SC), or oral (OR) routes at 2 mg/kg. In the second group (n = 8),TAwas administered intravenously to each sheep at 2, 4, 8, and 16 mg/kg. Plasma samples were analyzed with a high‐performance liquid chromatography assay. Noncompartmental pharmacokinetic analyses were used to evaluate the data. The area under the concentration–time curves (AUC0−∞), elimination half‐life (t1/2ʎz), and the mean residence time (MRT) significantly differed among the administration routes at 2 mg/kg ofTA. FollowingIM,SC, andORadministrations,TAdemonstrated different peak concentrations (Cmax) and time to reachCmax(Tmax), with a bioavailability of 163%, 127%, and 107%, respectively. The dose‐normalizedAUC0−∞revealed a significant difference among the dose groups; however, the relationship between dose andAUC0−∞was linear. Botht1/2ʎzandMRTincreased depending on the dose. Although the total clearance (ClT) decreased depending on dose, the volume of distribution at steady‐state (Vss) increased. Tolfenamic acid indicated a long half‐life and high bioavailability followingIM,SC, andORadministrations at 2 mg/kg.TAexhibited linear kinetics and was well tolerated by the animals, except at 16 mg/kg. Thus,TAmay be used in different routes and doses (≤8 mg/kg) in sheep; however, further studies are needed to determine the clinical efficacy ofTAduring the inflammatory and painful conditions and the pharmacokinetics and safety of repeated administration in sheep.
Keywords: Analgesics; Cross-Over Studies; Sheep; Dose-Response Relationship, Drug; Drug Administration Routes; Biological Availability; Random Allocation; Area Under Curve; Animals; ortho-Aminobenzoates; Half-Life; 2. Zero hunger